Zachowanie należytej staranności i dobra wiara podatnika w kontekście prawa do obniżenia kwoty podatku należnego o kwotę podatku naliczonego - Sekulski, Piotr; Zielińska, Dominika (Kwartalnik Prawa Podatkowego, 2016)
The aim of the article is to present the principles of the due diligence and good faith of the VAT payer regarding his right to reduce the amount of input tax by the amount of output tax. The principles, though of great importance for the economy, have not been defined in Polish tax law. The authors have therefore presented the abundant and wellestablished jurisprudence of the Polish courts and the European Court of Justice on this matter.